2017
DOI: 10.1556/004.2017.037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of arginase activity, nitric oxide and oxidative stress status in sheep with contagious agalactia

Abstract: It is known that inflammatory organ damages due to various agents, such as microorganisms including mycoplasmas, lead to oxidative stress. Nitric oxide (NO) functions as an antimicrobial agent, and arginase decreases proinflammatory cytokine release. There are very few studies on arginase activity, NO level and oxidative stress status in mycoplasmal infections. Therefore, the aim of this study was to evaluate erythrocyte arginase activity, plasma NO level and oxidative stress status in sheep with contagious ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In consequence, large amounts of NO are synthesized, exceeding the physiological NO production by up to 1000-fold (Wallace 2005;Sharma et al, 2007). It was reported that NO concentrations in animals with bacterial (Nisbet et al, 2007;Li et al, 2010;Hanedan et al, 2017), viral (Kandemir et al, 2011;Bozukluhan et al, 2013) and parasitic diseases (Kontas and Salmanoglu 2006) increased compared to healthy controls. It was determined that NO concentrations increased in cattle with TRP (Atakisi et al, 2010) and traumatic pericarditis (Ozkan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consequence, large amounts of NO are synthesized, exceeding the physiological NO production by up to 1000-fold (Wallace 2005;Sharma et al, 2007). It was reported that NO concentrations in animals with bacterial (Nisbet et al, 2007;Li et al, 2010;Hanedan et al, 2017), viral (Kandemir et al, 2011;Bozukluhan et al, 2013) and parasitic diseases (Kontas and Salmanoglu 2006) increased compared to healthy controls. It was determined that NO concentrations increased in cattle with TRP (Atakisi et al, 2010) and traumatic pericarditis (Ozkan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that NO has pro-inflammatory and injurious effects on several systems (Van Der Vielt et al, 2000;Sharma et al, 2007). NO is known to play a major role in the primary defence against several species of bacteria (Degroote and Fang 1999;Nisbet et al, 2007;Hanedan et al, 2017), viruses (Issi et al, 2010;Kandemir et al, 2011) and parasites (Kontas and Salmanoglu 2006;Hanedan et al, 2015). NO also regulates the motility of the rumen and reticulum in cattle (Onaga et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Other countries from Southeast Europe (Bulgaria, Croatia, Slovenia, Montenegro, Bosnia and Herzegovina, and Serbia) and the Maghreb (Tunisia, Algeria, Libya) did not report any CA and some Eastern Mediterranean countries (Lebanon, Egypt, Turkey) either gave no information or no reports. However, the scientific literature does feature clinical cases or surveys of CA for several of these countries: (i) Bosnia and Herzegovina where a survey on respiratory and ocular samples evidenced a few cases of Mmc, Mcc, and Mp in both sheep and goats,46 (ii) North Macedonia, where several Ma CA cases in sheep and goats were reported,127 and (iii) Turkey, where Ma appeared to be dominant in both sheep and goats (15% Ma -positive in 234 individual samples) 45,128. This clearly underlines how, despite mandatory notification, CA remains overlooked by national veterinary services.
Figure 1Distribution of contagious agalactia in 2014 and 2018 in Mediterranean countries according to OIE reporting.
…”
Section: Diagnosismentioning
confidence: 99%
“…It is principally caused by a specific pathogen, Mycoplasma agalactiae, and characterised by lesions of the mammary glands, joints and eyes (4). According to the World Organisation for Animal Health (OIE) and as borne out by numerous research undertakings, contagious agalactia of sheep and goats is endemic in Greece (13), Italy (6), Iran (14,24,25), Spain (2,11), Turkey (15) and Romania (20). Localised foci of the disease have also been described in Ghana and Israel (1).…”
Section: Introductionmentioning
confidence: 99%